1979
DOI: 10.1111/j.1365-2230.1979.tb01592.x
|View full text |Cite
|
Sign up to set email alerts
|

A clinical double-blind trial of topical haloprogin and miconazole against superficial fungal infections

Abstract: Summary A clinical double‐blind trial of topical haloprogin ointment and miconazole cream was carried out against superficial fungal infections of the skin and erythrasma. The trial showed that haloprogin had the same broad range of activity as miconazole being effective against dermatophyte, pityriasis versicolor, Candida and erythrasma infections. Patient acceptability was not as good for haloprogin as it was for miconazole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1980
1980
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Miconazole was superior to placebo, and efficacy was similar to clotrimazole 1%, haloprogin 1% and sulconazole 1% (no P ‐values) . Overall, mycological cure ranged from 81% to 100%; with 96%–100% mycological cure for infants with diaper dermatitis and 81%–100% for adults with Candida at various body sites .…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Miconazole was superior to placebo, and efficacy was similar to clotrimazole 1%, haloprogin 1% and sulconazole 1% (no P ‐values) . Overall, mycological cure ranged from 81% to 100%; with 96%–100% mycological cure for infants with diaper dermatitis and 81%–100% for adults with Candida at various body sites .…”
Section: Resultsmentioning
confidence: 98%
“…Overall, 41 articles investigated topical therapy for cutaneous candidiasis including 2711 patients in 35 RCTs (LE: 1B) and seven prospective blinded or open‐label trials (LE: 2B), of which one article reported two trials in the same article (LE: 1B and 2B) (Table ). In total, 17 different single‐drug and four combination therapies were investigated including clotrimazole (12 studies, LE: 1B or 2B), nystatin (ten studies, LE: 1B or 2B), miconazole (eight studies, LE: 1B), halcinonide–neomycin–amphotericin B (three studies, LE: 1B), ciclopirox (two studies, LE: 1B and 2B), haloprogin (two studies, LE: 1B), halcinonide–neomycin–nystatin (two studies, LE: 1B), naftifine (two studies, LE: 1B), sulconazole (two studies, LE: 1B), mupirocin (two studies, LE: 1B or 2B) and a number of drugs tested in a single study (Table ). In 50% of the studies, the type of Candida was specified by microscopy and/or culture and the majority recorded C. albicans , whereas three studies also found a few patients with C. parapsilosis or C. tropicalis .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This difference was not statistically significant. Another clinical study comparing haloprogin with miconazole recorded no significant superiority for either compound when cure was assessed by negative culture results (Clayton et al, 1979).…”
Section: Discussionmentioning
confidence: 99%